2012
DOI: 10.1126/scisignal.2003543
|View full text |Cite
|
Sign up to set email alerts
|

Rho GEFs and Cancer: Linking Gene Expression and Metastatic Dissemination

Abstract: Guanine nucleotide exchange factors (GEFs) that promote GTP loading onto the guanosine triphosphatases (GTPases) Rho and Rac are prominent players in cancer progression. Recent studies have highlighted the relevance of several GEFs, including the phosphatidylinositol 3,4,5-trisphosphate Rac exchangers P-Rex1 and P-Rex2a, in breast tumorigenesis. New evidence suggests that the exchange factors Vav2 and Vav3 play synergistic roles in breast cancer by sustaining tumor growth, neoangiogenesis, and metastasis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…Surprisingly, we found that ECT2 is required for E6AP regulation of EGF-induced RhoA and Cdc42 activation but not Rac1 activation. As E6AP downregulation still increases Rac1 activity, other GEFs are likely to mediate Rac1 activation and indeed, others GEFs are highly expressed in human breast cancers (49). For example, the GEF Tiam1 is highly expressed in high-grade breast tumors, where it mediates migration and invasion (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found that ECT2 is required for E6AP regulation of EGF-induced RhoA and Cdc42 activation but not Rac1 activation. As E6AP downregulation still increases Rac1 activity, other GEFs are likely to mediate Rac1 activation and indeed, others GEFs are highly expressed in human breast cancers (49). For example, the GEF Tiam1 is highly expressed in high-grade breast tumors, where it mediates migration and invasion (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…The remaining four genes VAV2 (VAV guanine nucleotide exchange factor 2), ASNS (asparagine synthesis), DNMT3B (DNA methyltransferase 3 beta), and AURKA (Aurora kinase A) not only all promote PC pathogenesis but also play a role in the development of CRPC (Gravina et al ., 2011; Magani et al ., 2017; Mosquera et al ., 2013; Sircar et al ., 2012). VAV2 is a coactivator of androgen receptor (AR) and sustains AR signaling under androgen deprivation therapy (ADT) (Magani et al ., 2017); it also promotes angiogenesis and metastasis (Barrio‐Real and Kazanietz, 2012). AURKA plays a critical role in mitosis (Dominguez‐Brauer et al ., 2015; Plotnikova et al ., 2015) and promotes the development of neuroendocrine PC under ADT (Beltran et al ., 2011; Mosquera et al ., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the role of Rho GEFS in cancer is emerging, including Vav2 (ref. 68). Moreover, Vav2 recently was shown to be required for lungspecific metastasis of breast cancer 69 .…”
Section: Discussionmentioning
confidence: 99%